2013
DOI: 10.1371/journal.pone.0054122
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C Regulates Human Pluripotent Stem Cell Self-Renewal

Abstract: BackgroundThe self-renewal of human pluripotent stem (hPS) cells including embryonic stem and induced pluripotent stem cells have been reported to be supported by various signal pathways. Among them, fibroblast growth factor-2 (FGF-2) appears indispensable to maintain self-renewal of hPS cells. However, downstream signaling of FGF-2 has not yet been clearly understood in hPS cells.Methodology/Principal FindingsIn this study, we screened a kinase inhibitor library using a high-throughput alkaline phosphatase (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
74
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 61 publications
4
74
0
Order By: Relevance
“…T he balance between self-renewal and differentiation of human pluripotent stem (hPS) cells, including embryonic stem (hES) and induced pluripotent stem cells, is controlled by various signal pathways [1][2][3][4][5][6][7][8], including transforming growth factor-b/activin A/Nodal [9][10][11], sphingosine-1-phosphate/platelet-derived growth factor [12], insulin growth factor (IGF)/insulin [13], and fibroblast growth factor-2 (FGF-2) [14][15][16][17]. In particular, FGF-2 signaling appears indispensable to maintain the undifferentiated state of hPS cells [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…T he balance between self-renewal and differentiation of human pluripotent stem (hPS) cells, including embryonic stem (hES) and induced pluripotent stem cells, is controlled by various signal pathways [1][2][3][4][5][6][7][8], including transforming growth factor-b/activin A/Nodal [9][10][11], sphingosine-1-phosphate/platelet-derived growth factor [12], insulin growth factor (IGF)/insulin [13], and fibroblast growth factor-2 (FGF-2) [14][15][16][17]. In particular, FGF-2 signaling appears indispensable to maintain the undifferentiated state of hPS cells [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the ERK-1/2 pathway has reported to have diverse roles in hPS cells, such as self-renewal, cell attachment, and cell differentiation [2,[25][26][27]. FGF-2 also induces inactive phosphorylation of glycogen synthase kinase-3 (GSK-3) [1,3,4,28] of which function has been reported to be controversial for self-renewal of hPS cells [29,30]. Moreover, we have recently reported that FGF-2 induces protein kinase C (PKC), which leads to phosphorylation of GSK3b [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human ES cell line, H9 (WA09, WISC Bank, WiCell Research Institute, Madison, WI, USA) was routinely maintained on mouse embryo fibroblast feeder cells inactivated by g-irradiation (MEF CF-1, Applied StemCell, Inc., CA, USA) in a hESC expansion medium (KSR-based medium) consisting of DMEM/F12 medium (Life Technologies, CA, USA) supplemented with 20% KSR (Life Technologies Ltd, Paisley, UK), 0.1 mM 2-mercaptoethanol (Sigma, St. Louis, MO, USA), 2 mM L-glutamine (Gibco, NY, USA), 0.1 mM non-essential amino acids (Gibco), and 5 ng/ ml human recombinant FGF-2 (Katayama Kagaku Kogyo, Japan) as previously described (Kinehara et al, 2013). The cells were split at a ratio of 1:8-1:10 every 6-7 days.…”
Section: Cell Culturementioning
confidence: 99%
“…Trunk NC cells migrate along the dorsal and lateral pathway and ously reported that culture in the presence of BMP4 in combination with FGF-2 induces the up-regulation of NC marker genes, including AP2a and P0 protein, during the differentiation of mouse embryonic stem cells (ESCs) into NC cells under chemically defined conditions (Aihara et al, 2010, Furue, 2012. Because culture systems for the stable expansion of human pluripotent stem cells had been developed (Amit et al, 2000, Furue et al, 2008, Kinehara et al, 2013, in vitro studies producing NC cells from human pluripotent stem cells have been reported (Fukuta et al, 2014, Lee et al, 2010, Menendez et al, 2013, Menendez et al, 2011. Dalton et al (Menendez et al, 2013, Menendez et al, 2011 have demonstrated that a combination of Wnt activation and Smad inhibition under serum-free culture conditions directs the differentiation of human ESCs (hESCs) and induced pluripotent stem cells into NC stem cells (NCSCs).…”
Section: Introductionmentioning
confidence: 99%